Partnerships without polycentricity? Cybersecurity governance in the Indo-Pacific - Sukma, Isti Marta (Society Register, 2026)
Cybersecurity governance in the Indo-Pacific increasingly relies on both public–private partnerships (PPPs) and polycentric governance arrangements, yet the relationship between these two frameworks remains empirically under-examined. Policy discourse and scholarship frequently conflate PPPs with polycentricity, obscuring their distinct governance functions. This study employs comparative qualitative content analysis of national cybersecurity strategy documents from Australia, Japan, and Singapore (2015–2025), supplemented by regional and geopolitical reference documents. Using a theory-driven codebook with 22 codes across six thematic clusters, 573 text segments were systematically coded in Taguette and analyzed through within-case interpretation and cross-case comparison. The analysis demonstrates that PPPs function primarily as operational mechanisms for information sharing, incident response, and co-investment within state-led frameworks. By contrast, polycentric governance features such as overlapping jurisdictions, multistakeholder involvement, and decentralized decision-making emerge independently through international cooperation, regional initiatives, and multi-actor regulatory platforms. The three cases reveal distinct governance configurations: Japan’s technocratic polycentricity, Australia’s resilience-oriented model, and Singapore’s regionally projected governance, all positioned between U.S. multistakeholder polycentricity and China’s centralized framework. This article provides the first systematic empirical comparison disentangling PPPs from polycentric governance in Indo-Pacific cybersecurity strategies, offering a more precise analytical framework for comparative governance research.